2022
DOI: 10.1111/1460-6984.12842
|View full text |Cite
|
Sign up to set email alerts
|

Embedding key word sign prompts in a shared book reading activity: The impact on communication between children with Down syndrome and their parents

Abstract: Background: Children with Down syndrome have speech and language difficulties that are disproportionate to their overall intellectual ability and relative strengths in the use of gesture. Shared book reading between parents and their children provides an effective context in which language development can be facilitated. However, children with Down syndrome often take a passive role in shared book reading and the use of key word signing (KWS) as a shared book reading technique has never been investigated. Aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…Burgoyne and Cain (2022) reported that children with DS produced significantly more utterances, significantly more words and more different words when parents used question prompts compared to the typical reading condition. Frizelle et al (2022) found that children attempted to sign significantly more in the signed than unsigned condition (see Supplementary Table 1).…”
Section: Non-intervention Sbr Studiesmentioning
confidence: 97%
See 3 more Smart Citations
“…Burgoyne and Cain (2022) reported that children with DS produced significantly more utterances, significantly more words and more different words when parents used question prompts compared to the typical reading condition. Frizelle et al (2022) found that children attempted to sign significantly more in the signed than unsigned condition (see Supplementary Table 1).…”
Section: Non-intervention Sbr Studiesmentioning
confidence: 97%
“…Three non-intervention studies used experimental (Burgoyne and Cain, 2022;Frizelle et al, 2022) or observational (Hilvert et al, 2022) designs to investigate SBR interactions between children with DS and their parents. The number of participants ranged from 8 to 15.…”
Section: Non-intervention Sbr Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, there is widespread evidence that when their development is adequately supported individuals with Down syndrome can live happy and meaningful lives (Skotko et al, 2016). In addition, providing them with education in inclusive rather than separate classrooms brings benefits in linguistic and literary skills (van Herwegen et al, 2018), and rich home literacy environments can lead to significant improvements in linguistic development (Ricci, 2011), especially if parents adopt a more interactive reading style (Frizelle et al, 2022).…”
Section: 1down Syndrome and Home Literacy Environmentsmentioning
confidence: 99%